Configurational Forces in Bond Order Potentials - Birang Oskouei, Seyedehelmira; Smith, Ana-Suncana; Steinmann, Paul (Proceedings in Applied Mathematics and Mechanics, 2021)
In this contribution, a configurational mechanics framework is elaborated to assess the applicability of atomistic configurational forces in fracture of crystalline lattices. To this end, an analytical interatomic potential is reformulated in terms of the material positions occupied by the atoms participating in two- and three-body interactions. It is demonstrated that such a potential satisfies the requirements of invariances i.e., translational, rotational and parity. The focus of this work is developing the configurational setting for the bond order Tersoff potential. Two-dimensional pre-cracked mono-layer graphene modelled with the Tersoff potential is chosen to study the configurational force approach in determining energy release during crack propagation into the lattice.<br